Mortality occurrence and pathogen detection in Crassostrea gigas and Mytilus galloprovincialis close-growing in shallow waters (Goro lagoon, Italy) - Domeneghetti, Stefania; Varotto, Laura; Civettini, Michele; Rosani, Umberto; Stauder, Monica; Pretto, Tobia; Pezzati, Elisabetta; Arcangeli, Giuseppe; Turolla, Edoardo; Venier, Paola; PALLAVICINI, Alberto (Fish & Shellfish Immunology, 2014)
The complex interactions occurring between farmed bivalves and their potential pathogens in the circumstances of global climate changes are current matter of study, owing to the recurrent production breakdowns reported in Europe and other regions of the world. In the frame of Project FP7-KBBE-2010-4 BIVALIFE, we investigated the occurrence of mortality and potential pathogens during the Spring-Summer transition in Crassostrea gigas and Mytilus galloprovincialis cohabiting in the shallow waters of one northern Italian lagoon (Sacca di Goro, Adriatic Sea) and regarded as susceptible and resistant species, respectively. In 2011, limited bivalve mortality was detected in the open-field trial performed with 6-12 month old spat whereas subsequent trials with 2-3 month old spat produced almost complete (2012) and considerable (2013) oyster mortality. Macroscopical examination and histology excluded the presence of notifiable pathogens but, in the sampling preceding the massive oyster spat mortality of 2012, a μdeleted variant of OsHV-1 DNA was found in wide-ranging amounts in all analyzed oysters in conjunction with substantial levels of Vibrio splendidus and Vibrio aestuarianus. The large oyster spat mortality with borderline OsHV-1 positivity recorded in 2013 supports the multi-factorial etiology of the syndrome. This is the first report of a OsHV-1 (under a form interpreted as the variant μVar) in the Goro lagoon. Transcriptional host footprints are under investigation to better understand the bivalve response to environmental factors, included viral and bacterial pathogens, in relation to the observed mortalities.